Nathaniel Mackey, destination out : essays on his work - Heuving, Jeanne, 1951- (Contemporary North American poetry series., 2021)
"As the first book to concentrate solely on the work of poet, novelist, literary critic, and editor Nathaniel Mackey, Nathaniel Mackey, Destination Out will make an important contribution to African American and Contemporary American literary and poetry criticism. Heuving provides an overview of Mackey's biography, work, and critical reception of his work, then brings together new and already important criticism from the field from scholars such as Fred Moten, Rachel Blau DuPlessis, and Peter O'Leary. Mackey cites poets William Carlos Williams and Amiri Baraka, in addition to jazz musicians John Coltrane and Don Cherry, as early influences in his exploration of how language can be infused and informed by music. Indeed, Mackey has broadcast jazz and world music as a DJ on local radio since the late 1970s, an endeavor he describes as similar to that of bringing together journal issues during his long tenure as the editor of Hambone magazine. About his own writing, he has said, "I try to cultivate the music of language, which is not just sounds. It's also meaning and implication. It's also nuance. It's also a kind of angular suggestion." In keeping with this melding of language and music, Heuving's volume is organized according to three distinct focuses of Mackey's work, which is especially useful for newcomers: myth, literature, and seriality; music, performance, and hybridity; and improvisation, what-saying, and so what? The authors the last section choose unconventional modes of essay writing, imitating Mackey's work even as they engage in criticism. Together, the volume represents an essential addition to the field"--